Gender wage gaps and economic crisis in Greece. Issue 2 (4th March 2019) - Agiomirgianakis, George; Bertsatos, Georgios; Tsounis, Nicholas
ABSTRACT: We examine gender wage gap (GWG) in Greece for 2013, by using a survey data set. Our findings show first, that the unadjusted GWG is 15.3%, while European Commission reports a value of 15%. Secondly, we derive the 'adjusted' GWG, using the Oaxaca and Ransom (OR) and the Juhn, Murphy and Pierce (JMP) methods to be ranging from 10% to 13.6%. Thirdly, looking into the behaviour of the full population, we find a decreasing trend for the discrimination effects, an increasing trend for the residuals effects and a 'random' endowments effects while moving to higher deciles. These three effects are associated to the economic crisis 2008–2015. Fourthly, our findings do not show evidence of either a 'glass ceiling' effect or a 'sticky floor' effect. Finally, that there is strong evidence that investing in higher education reduces the wage discrimination between sexes.